Exploration of Arrhenius activation energy on hybrid nanofluid flow over a curved stretchable surface. Issue 12 (13th August 2021) - Varun Kumar, R.S; Alhadhrami, A.; Punith Gowda, R.J.; Naveen Kumar, R.; Prasannakumara, B.C.
Abstract: Scientists and engineers have experimentally noticed that the heat transfer is essential for preeminence of multi scale production. Thermal properties are naturally accomplished via continuous phase liquids. Its importance is nevertheless constrained by the low capacity for heat transfer. Consequently, the increased heat transference phenomenon must be employed to accomplish the expected results. In this regard, the nature of the Arrhenius activation energy in the flow of hybrid nanoliquid over a curved stretchable surface (CSS) in the presence of exponential heat generation is scrutinized. The fluid suspended with Manganese zinc ferrite ( M n Z n F e 2 O 4 ) and Nickel zinc ferrite (NiZnFe2 O4 ) as nanoparticles along with Kerosene oil as a base liquid is accounted in this study. The described flow equations are transformed by using appropriate similarity variables and then they are tackled with Runge Kutta Fehlberg‐45 (RKF‐45) scheme by adopting shooting process. It can be concluded that, the increasing values of Biot number and heat source/sink parameter improves the thermal gradient. Further, hybrid nanofluid shows high heat transfer rate when compared to nanoliquid for improved values of heat source/sink parameter. Abstract : Scientists and engineers have experimentally noticed that the heat transfer is essential for preeminence of multi scale production. Thermal properties are naturally accomplished via continuous phase liquids. Its importance is nevertheless constrained by the low capacity for heat transfer. Consequently, the increased heat transference phenomenon must be employed to accomplish the expected results. In this regard, the nature of the Arrhenius activation energy in the flow of hybrid nanoliquid over a curved stretchable surface (CSS) in the presence of exponential heat generation is scrutinized.…